Manifestations of Existentialist Conflict in Aws Ibn Hajr’s L-Rhymed Poems - Mushtaq talib monem ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
The subject of conflict remains one of the important topics that have always held the same priority and significance in research and study, and this importance perhaps increases with the passage of time and its expiration, in accordance with new perspectives and contents that proportionally correspond to the nature of daily life on one hand, and the evolution of views, concepts, standards, and perspectives on the other hand. The theme of conflict manifests in various forms. It could be between humans and their own kind, or between them and non-rational beings represented by nature and animals. It often extends to the individual’s inner conflict with themselves, meaning that the individual enters into a conflict with themselves. This phenomenon is influenced by circumstances, context, and even daily living reality, which is what we perceive today in our natural lives. So, man, according to the philosophy of Martin Heidegger, is the only being capable of perpetually transcending himself towards the possible, thus achieving existence through it. Meanwhile, other entities do not possess the ability to transcend themselves as they are either animalistic or otherworldly. The primary idea of this research emerges from the Mu’allaqa of Tarafa Ibn al-Abd, carrying within it various visions, challenges, and manifestations. Additionally, numerous studies have been conducted from different perspectives, including the subject of conflict, which presents a single title but with various approaches. Consequently, I seek a poem to be suitable for the theme of conflict and find, many poems that can be sufficient, the L-Poem of Aws ibn Hajar is the most fertile, for various reasons such as the aspects which relates to the poet himself, the nature of the poem, its numerous elements of renewal, as well as its expression of the real situation and the image of that era. The poem of this research encompasses many manifestations of existential conflict within its folds, ranging from selfhood, isolation, rebellion against reality, victory for the self, to the ending with the dialectic of presence and absence. These are manifestations brought forth by the eternal conflict between the self and the other.